Geomorphological anthropogenic dynamics in the municipality of Chía (Cundinamarca, Colombia) (2022)
This article describes and analyzes the anthropogeomorphological interventions and changes in the territory of Chía, located in central Colombia in the Eastern Andean Mountain range. The research was based on the advances of the sub-discipline "anthropogeomorphology" and was elaborated from a documentary review, photo-interpretation of inputs, fieldwork and quantitative examination of data. The results show an account of human actions, with graphic examples of the phenomenon and characterizations at a scale of 1:10,000 for four reference periods (1940, 1977, 2000 and 2020); the patterns and trends of the interventions in relation to the natural morphogenic systems were also defined and the footprint of the anthropogeomorphs was estimated according to the magnitude of the excavations and artificial accumulations. We conclude on the current predominance of urbanogenic, transit, water management and waste modeling for the fluvial-lacustrine environments of the altiplano, while, on the mountainous flanks, the predominance of agro-genic and mining modeling is highlighted, with the increase of suburban morphologies.